DETERMINANTS OF KEY ENTREPRENEURIAL CHARACTERISTICS: A STUDY OF ENTREPRENEURIAL ATTITUDE OF AGRICULTURAL STUDENTS OF TELANGANA STATE - E. SREE CHARAN, A. MEENA, D.UTTEJ AND (The Journal of Research, PJTSAU, 2019)
The present study was carried out to study the Profile characteristics of Agricultural Students of Telangana State, to study the agreement among several rankers with respect to the characteristics-Risk Orientation , Achievement Orientation, Innovativeness, Market Orientation, Decision making ability, to identify the key Entrepreneurial characteristics. The study concluded that about 65.5% of the agricultural students were fromthe age group of 19-24 years, 40.8% were first born child,54% had first class marks & 23% had distinction, with low participation in extracurricular activities, 88.3 % of their fathers were literates and were engaged in government service and business, and 45.8 % of them are having 2.6 to 5 acres of land.Factor Analysis was done for extracting the key Entrepreneurial characteristics and Kendall’s Co-efficient of Concordance was used to test the agreement among several rankers. The result showed that there is strong agreement among the respondents with respect to ranking each of the attributes under Risk Orientation as Kendall’s W = 0.59 & moderate agreement with respect to ranking the attributes under Market Orientation with W= 0.292. There is no agreement among the respondents with respect to ranking each of the attributes under Achievement Orientation, Innovativeness, and Decision making ability since Kendall’s w is equal to 0.113, 0.182, and 0.064 respectively.Three key factors were extracted;finally ranking of the indicators has been made on the basis of factor scores. Further from the Kendall’s Co-efficient value it is concluded there is complete disagreement between the raters regarding each of the following - Agro based enterprise as the best option to earn money for landless rural people, Agro based enterprise can be a good source of income for low investors and establishment of Agro based enterprise is unproductive.